KADRLAR TAYYORLASHDA AXBOROT ISTEMOLI MADANIYATINING OʻRNI - Ramazonov, J.Dj. (SCIENCE and SOCIETY, 2025)
This article examines the role of information culture in the training of leaders, the psychological features of the formation of an information-demanding culture, the necessary characteristics of information culture today, the formation of an information-demanding culture and skills of youth based on The article discusses the requirements of the global era, as well as the psychological conditions necessary for the formation of these characteristics among young people, comments are given.
Keywords: audiovisual culture; logical culture; semiotic culture; conceptual and technological culture; information culture; terminological culture; communication culture; information worldview; information literacy; information; culture